Controversy About Management of Osteoarthritis with Disease-modifying Anti-rheumatic Drugs - CUI Hanshu; LIU Bin (Xiehe Yixue Zazhi)
Osteoarthritis (OA) is a degenerative joint cartilage disease characterized pathologically by osteophytes formation and subchondral bone damage. It leads to pain, stiffness, deformation and even disability in the patients, and increases the risk of comorbidities. As its pathophysiological mechanisms are not well understood, it is hard to identify the specific targets of OA and standardize its pharmacological treatments. Some scholars believe that synovial inflammation is the main factor of pain and progression of OA, so disease-modifying anti-rheumatic drugs (DMARDs) for inflammatory arthritis could be used to treat OA. However, others hold opposing views, arguing that inflammation is not the core driving factor of OA, and the available research results are not sufficient to support the application of DMARDs in OA. In addition, the side effects and monitoring requirements limit the application value of DMARDs in treatment of OA, especially for elderly OA patients with comorbidities. This article analyzes and discusses this debate based on the mechanisms of OA inflammation and pain, and in conjunction with relevant research findings from domestic and international studies.